Implementing Speech Community Strategy to Enhance Students’ English Speaking Ability - Huriyah Huriyah (Language Center of Islamic Institute of Uluwiyah, Mojokerto, Indonesia., 2015)
Implementing speech community strategy to enhance students English speaking ability. This classroom action research describes how the implementation of speech community strategy increases the students’ English speaking ability. The research stages consist of planning, implementing, observing, evaluating and reflecting. The study indicates that the providing of speech community can increase English speaking ability at students of SMA Sekar Kemuning Islamic Boarding School Cirebon